Proficiency of platelet parameters as an inexpensive efficient early marker for diagnosis of neonatal sepsis - Bagchi, Nilay Ranjan (International Journal of Research in Medical Sciences, 2023)
Background: Neonatal sepsis is an invasive serious infection which is life threatening if not treated early. Though blood culture is the gold standard for diagnosis but it yields positive results in fewer number of cases and it also time consuming. So it is requisite to ordain a cost effective and easy marker for its early diagnosis to initiate treatment to reduce the case fatality. Methods: A prospective study was done for 12 months upon 48 blood culture proven cases of neonatal sepsis. 48 normal babies were taken as control group. Platelet parameters were studied in all 96 babies of the study population. Results: It was found that thrombocytopenia, mean platelet volume (MPV), platelet large cell ratio (P-LCR) and mean platelet volume to total platelet count ratio (MPV/TPC) are early helpful markers for diagnosis of sepsis in neonates with p value of 0.0003, <0.0001, <0.0001 and <0.0001 respectively. MPV/TPC has the highest specificity (95.6%) with positive predictive value (90.2%). Conclusions: Platelet count and its indices are cheap, early and workable marker for diagnosis of neonatal sepsis.